Revolutions - Lowy, Michael; Recorded Books, Inc. (Chicago : Haymarket Books, 2020)
The photographs collected in this unique book provide a startling visual documentation of seminal revolutionary events, from the Paris Commune of 1871 through to a series of "Unfinished Revolutions", from May 1968 in France to the Zapatista uprsing in ther mid-1990s. The immediacy of the images tells the story of these struggles in a way that texts rarely can, with revolutions appearing as complex and messy events driven by the actions of real, breathing humans who make their own history. Commentary on the images is provided by leading historians Gilbert Achcar, Enzo Traverso, Janette Habel, and Pierre Rousset, and Michael LOwy. This edition includes a new afterword by the author.
Title from resource description page (Recorded Books, viewed June 22, 2020).
eBooks on EBSCOhost
Keywords: History; Histoire; history (discipline); HISTORY / Revolutionary; History